Palm Oil Quality Based on Free Fatty Acid Using SVM - Prayogi, Andi; Aly, Moustafa H.; Ikhwan, Ali; Pane, Muhammad Akbar Syahbana; Siregar, Ratu Mutiara (Universitas Nusantara PGRI Kediri, 2025)
Background: Palm oil is one of the key commodities in both the food and non-food industries, with its quality largely influenced by the level of Free Fatty Acid (FFA). Obejctive: High FFA content can reduce the stability and market value of the oil. Classify palm oil quality based on FFA levels using the Support Vector Machine (SVM) algorithm. Methods: FFA levels were measured across multiple samples with varying usage frequencies (0, 5, 7, and 9 cycles) using the alkalimetric titration method. The measured data was categorized as